2005
DOI: 10.1152/ajpendo.00009.2005
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and cellular plasticity in white adipose tissue I: effects of β3-adrenergic receptor activation

Abstract: Selective agonists of beta(3)-adrenergic receptors (Adrb3) exhibit potent anti-diabetes properties in rodent models when given chronically, yet the mechanisms involved are poorly understood. A salient feature of chronic Adrb3 activation is pronounced remodeling of white adipose tissue (WAT), which includes mitochondrial biogenesis and elevation of metabolic rate. To gain insights into potential mechanisms underlying WAT remodeling, the time course of remodeling induced by the Adrb3 agonist CL-316,243 (CL) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
229
1
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(266 citation statements)
references
References 40 publications
(39 reference statements)
31
229
1
5
Order By: Relevance
“…Recently, Kosteli and colleagues demonstrated that acute weight loss is unexpectedly associated with a rapid - albeit transient - lipolytic-driven recruitment of macrophages into AT (39), thereby confirming similar reports by Granneman and colleagues (44).…”
Section: The Intricate Dynamics Of At Remodelingsupporting
confidence: 71%
“…Recently, Kosteli and colleagues demonstrated that acute weight loss is unexpectedly associated with a rapid - albeit transient - lipolytic-driven recruitment of macrophages into AT (39), thereby confirming similar reports by Granneman and colleagues (44).…”
Section: The Intricate Dynamics Of At Remodelingsupporting
confidence: 71%
“…The key support that the browning of white adipocytes is dependent on β 3 -adrenoceptor stimulation (for review, see Bartness et al 26,27 ) rests on the findings that cold-exposed β 3 -adrenoceptor knockout mice compared with their wild-type controls have white adipocytes that: (a) do not express UCP-1, (b) have either reduced or no production of other factors associated with the 'thermogenic program' such as PGC1α, CIDEA and C/EBPβ and (c) have decreased morphological brown-type adipocyte characteristics such as decreases in the number of multilocular cells. [31][32][33] Although it has been suggested that because chronic administration of the β 3 -adrenoceptor agonist CL-316 243 differentially stimulates browning across WAT depots, 31 this does not necessarily imply that there is a cell autonomous process at work in browning independent of the CNS control of sympathetic drive as some suggest. 1 This effect could easily be explained in terms of the number and affinity of β 3 -adrenoceptors that occur across WAT depots (for example, see Bowen et al, 34 Leibel and Hirsch, 35 Umekawa et al 36 ) or the balance between lipolytic/browning β 3 -adrenoceptors and antilipolytic (and perhaps anti-browning) α 2 -adrenoceptors (for review, see Lafontan et al 37,38 ).…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was isolated using the single-step TRI reagent and 1 μg RNA was reverse-transcribed into cDNA. In brief, the isolated RNA was dissolved in sterile water and 2.5 mmol/l Mg 2+ , 1 mmol/l dNTPs, 0.5 μg oligodT 15 , 25 U AMV reverse transcriptase, 10× RT buffer, giving a final volume of 20 μl. The sample was incubated at 25°C (10 min), 42°C (60 min) and 99°C (5 min).…”
Section: Methodsmentioning
confidence: 99%
“…Promoting mitochondrial biogenesis by upregulation of the Ppargc1a pathway has been suggested as a strategy for preventing and reversing insulin resistance, obesity and diabetes [3,9,10]. In this regard, several drugs have been tested, such as metformin and 5-aminoimidazole-4-carboxamide ribonucleoside [11], the Pparg agonist pioglitazone/rosiglitazone and Ppara agonist WY-14,643 [12][13][14], as well as beta 3-adrenergic receptors agonist CL-316,243 [15] and oestrogen-related receptor α [16].…”
Section: Introductionmentioning
confidence: 99%